2017
DOI: 10.1039/c6ra26356a
|View full text |Cite
|
Sign up to set email alerts
|

Chelating magnetic nanocomposite for the rapid removal of Pb(ii) ions from aqueous solutions: characterization, kinetic, isotherm and thermodynamic studies

Abstract: Fe3O4@GMA–AAm nanocomposite as a novel adsorbent with high adsorption capacity for rapid removal of Pb2+ from aqueous media was synthesized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 48 publications
(49 reference statements)
2
25
0
Order By: Relevance
“…From Figure , four sharp peaks were observed which are indicating the presence of crystalline iron oxide (Fe 3 O 4 ) particles with 2θ values of 30.5, 35.94, 43.5, 57.41, and 63.1 corresponding indices of (220), (311), (400), (511), and (440) . The average diameter of the particles of 24.5 nm which was calculated from the Debye–Scherrer equation D=kλβ cosθ where k is Scherrer constant (considered being 0.89), λ is wavelength of X‐ray, β is the peak width of the half maximum, and θ is the Bragg diffraction angle of magnetic Chitosan.…”
Section: Resultsmentioning
confidence: 56%
See 2 more Smart Citations
“…From Figure , four sharp peaks were observed which are indicating the presence of crystalline iron oxide (Fe 3 O 4 ) particles with 2θ values of 30.5, 35.94, 43.5, 57.41, and 63.1 corresponding indices of (220), (311), (400), (511), and (440) . The average diameter of the particles of 24.5 nm which was calculated from the Debye–Scherrer equation D=kλβ cosθ where k is Scherrer constant (considered being 0.89), λ is wavelength of X‐ray, β is the peak width of the half maximum, and θ is the Bragg diffraction angle of magnetic Chitosan.…”
Section: Resultsmentioning
confidence: 56%
“…From Figure 5, it is reported that the broad peak at the wavelength of 3313. 71 76,77 Overall the FTIR peaks analyses the evidence of bonds and functional groups presents in the magnetic adsorbent and also provides the necessary functional NAH bond from which the Cr(VI) were to be adsorbed. 14 The ANH 2 functional group present in the outer layer of chitosan affected by addition of free H 1 ion which is present in water and forming ANH 1 3 .…”
Section: Characteristics Of Prepared Magnetic Chitosanmentioning
confidence: 99%
See 1 more Smart Citation
“…Next, it was needed to determine how fast NPLD can take up Pb 2+ from water and therefore we have performed a kinetic adsorption study [75][76][77] for Pb(II). To determine the effectiveness of the NPLD nanomaterial for adsorbing lead with time, a kinetic adsorption isotherm of Pb(II) on NPLD was acquired using PbCl 2 solution, in which the concentration of Pb 2+ was 100 mg L À1 .…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, new technologies able to degrade these complex pollutants are needed. These include advanced oxidation processes (AOPs) [1][2][3], adsorption methods [4][5][6] and photocatalytic processes [7][8][9].…”
Section: Introductionmentioning
confidence: 99%